PENGARUH KEMAMPUAN, MOTIVASI DAN LINGKUNGAN TERHADAP PRESTASI KERJA PEGAWAI DINAS PERHUBUNGAN KOMUNIKASI DAN INFORMATIKA KOTA BANJARMASIN - Normajatun Normajatun; Abdul Haliq (AS-SIYASAH: Jurnal Ilmu Sosial Dan Ilmu Politik, 2016)
This study aimed to know the description of : 1) ability, motivation and environment as well as the aachievemenet of the work of employee, and 2) the influence of the ability, motivation, and environmenet partially nor simultan against employees on the work achievement of Departement of Tranfort Communication and Informatics of the city Of Banjarmasin.. This research method using the associative of research type of correlation. The subjects is the entire officers and using simple random sampling techniques to take sample. Data were collected techniquues by using a questionnaire and further analyzed by using multiple linier regression techniques. Data processing using the help of the program SPSS (Statistical Product Service Solution) for Window 21.0. The research results of the descriptive analysis showed, ability and work achievement, which is nice. While the motivation of employees and the environmenet are included in the catagories that are very nice. The results of the statistical analysis in partial showed the ability and motivation has no effect againist the employees work achievement, while the environment influence on work achievement. The simultaneous ability, motivation, and environment effect on employees work achievement